Hubungan Pemahaman dan Harapan Orang Tua dengan Pembelajaran Berbasis Proyek Ditinjau dari Usia dan Status Pendidikan - Indrawati, Elly; Raharjo, Tri Joko; Formen, Ali (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Parent’s profile is important in early childhood development. The purposes this research were to analyze acorrelation 1) parents’ understanding with PjBL; 2) parents’ understanding with PjBL in view of parents’ age 3) parents’ expectation with PjBL; 4) parents’ expectation with PjBL in view of parents’ age; 5) parents’ understanding and expectation with PjBL; 6) parents’ understanding and expectation with PjBL in view of parents’ education status. Quantitative method used in this research.The results of this research: 1) There is a correlation between parents’ understanding with project based learning with value 0,531; 2) There is a correlation between parents’ understanding with project based learning in view of parents’ age with value 0,532; 3) There is a correlation between parents’ expectation with PjBL with value 0,513; 4) There is a correlation between parents’ expectation with project based learning in view of parents’ age with value 0,510; 5) There is a correlation between parents’ understanding and expectation with PjBL with value 0,668; 6) There is a correlation between parents’ understanding and expectation with PjBL in view of parents’ education status with value 0,794. The conclusion of this research was profile influenced project based learning in kindergarten.